Nigella sativa Seed Powder Supplementation Mitigates Oxidative Stress Biomarkers Alterations in Very Virulent Infectious Bursal Disease Virus-Infected Chickens - Muhammed, Muhammed Shuaib; Orakpoghenor, Ochuko; Oladele, Sunday Blessing; Mohammed, Bisalla; Musa, Ibrahim Waziri (Universitas Airlangga, 2026)
Oxidative imbalance plays a key role in the pathology associated with highly virulent infectious bursal disease virus infection in chickens; however, nutritional strategies to limit this damage remain insufficiently explored. This study evaluated the influence of dietary Nigella sativa seed powder on selected oxidative biomarkers in experimentally infected cockerels. One-hundred-day-old birds were randomly distributed into five groups: uninfected controls, infected controls, seed powder supplementation alone, short-term supplementation with a viral challenge, and continuous supplementation with a viral challenge. The supplement was incorporated into the feed for either 7 or 42 days, while infection was induced orally at 28 days of age. Serum analysis revealed that viral infection reduced superoxide dismutase activity while increasing catalase activity, glutathione peroxidase activity, and lipid peroxidation levels. Birds receiving continuous supplementation showed markedly attenuated alterations compared to the untreated infected groups. These findings indicate that Nigella sativa seed powder effectively moderated virus-associated oxidative disturbances by supporting endogenous antioxidant defenses and limiting membrane lipid damage, highlighting its potential value as a functional dietary intervention in infected poultry.